Serologic evidence of exposure to Rift Valley fever virus detected in Tunisia. (January 2016) - Bosworth, A.; Ghabbari, T.; Dowall, S.; Varghese, A.; Fares, W.; Hewson, R.; Zhioua, E.; Chakroun, M.; Tiouiri, H.; Ben Jemaa, M.; Znazen, A.; Letaief, A.
Abstract: Rift Valley fever virus (RVFv) is capable of causing dramatic outbreaks amongst economically important animal species and is capable of causing severe symptoms and mortality in humans. RVFv is known to circulate widely throughout East Africa; serologic evidence of exposure has also been found in some northern African countries, including Mauritania. This study aimed to ascertain whether RVFv is circulating in regions beyond its known geographic range. Samples from febrile patients ( n  = 181) and nonfebrile healthy agricultural and slaughterhouse workers ( n  = 38) were collected during the summer of 2014 and surveyed for exposure to RVFv by both serologic tests and PCR. Of the 219 samples tested, 7.8% of nonfebrile participants showed immunoglobulin G reactivity to RVFv nucleoprotein and 8.3% of febrile patients showed immunoglobulin M reactivity, with the latter samples indicating recent exposure to the virus. Our results suggest an active circulation of RVFv and evidence of human exposure in the population of Tunisia.